Nonequilibrium thermodynamic modeling of carbon partitioning in quench and partition (Q&P) steel. (1st April 2018) - Behera, Amit K.; Olson, G.B.
Abstract: The influence of partitioning temperature on carbon partitioning during the quench and partition (Q&P) cycle and the associated non-equilibrium phase transformation thermodynamics have been investigated. Lower partitioning temperatures are reported to result in higher carbon partitioning with varying austenite phase fraction. Thermodynamic simulations considering para-equilibrium conditions with an added temperature-dependent effective stored energy contribution have been shown to reasonably predict the retained austenite carbon content. The developed models have been validated with new alloy compositions, QP cycles and data from existing literature. Graphical abstract: Image 1